The Superstatistical Nature and Interoccurrence Time of Atmospheric Mercury Concentration Fluctuations. Issue 2 (19th January 2018) - Carbone, F.; Bruno, A. G.; Naccarato, A.; De Simone, F.; Gencarelli, C. N.; Sprovieri, F.; Hedgecock, I. M.; Landis, M. S.; Skov, H.; Pfaffhuber, K. A.; Read, K. A.; Martin, L.; et al.
Abstract: The probability density function (PDF) of the time intervals between subsequent extreme events in atmospheric Hg 0 concentration data series from different latitudes has been investigated. The Hg 0 dynamic possesses a long‐term memory autocorrelation function. Above a fixed threshold Q in the data, the PDFs of the interoccurrence time of the Hg 0 data are well described by a Tsallis q‐exponential function. This PDF behavior has been explained in the framework of superstatistics, where the competition between multiple mesoscopic processes affects the macroscopic dynamics. An extensive parameter μ, encompassing all possible fluctuations related to mesoscopic phenomena, has been identified. It follows a χ 2 distribution, indicative of the superstatistical nature of the overall process. Shuffling the data series destroys the long‐term memory, the distributions become independent of Q, and the PDFs collapse on to the same exponential distribution. The possible central role of atmospheric turbulence on extreme events in the Hg 0 data is highlighted. Key Points: Superstatistics of atmospheric Hg 0 concentration extremes is demonstrated via the probability density functions of the interoccurrence time The statistics of interoccurrence times has been related to the long‐term memory of Hg 0 concentrations via Tsallis q statistics Universal scaling in atmospheric Hg 0 concentration extremes was found, a possible link to atmospheric turbulence is suggested